Analisa Konfigurasi Jaringan FTTH dengan Perangkat OLT Mini untuk Layanan Indihome di PT. Telkom Akses Witel Semarang - Muliandhi, Puri; Faradiba, Erlian Husna; Nugroho, Bayu Adi (Elektrika, 2020)
The development of increasingly sophisticated technology follows the needs of the community, one of them in the telecommunications world is FTTH (Fiber to the Home) which is an optical signal delivery format from the center of the provider to the homes of costumers by using optical fiber as a medium of delivery. Delivery by using this FTTH technology can save costs and provide better service to customers. The study was conducted by interview and observation methods with network objects and FTTH components belonging to Telkom Semarang and through the literature method by searching some literature. FTTH configuration starts with the ONT to rosette connected using a patchcord cable then from rosette to OTP using an indoor cable then from OTP to ODP outside the home is connected using a dropcore cable. ODP itself is the result of the distribution of distribution cables/ aerial cables leading to ODC. ODC to STO/FTM/ODF using feeder cable. FTTH network is very effective to use, because it can use triple play services (telephone, internet and IPTV) with just 1ONT/ modem at the customer s side.